Mitochondrial calcium shapes B cell signaling and mitochondrial function - Taskiran, Hakan; Czeslik, Elena; Stark, Leonhard; Kläsener, Kathrin; Schnalzger, Theresa Elisa; Ruland, Jürgen; Reth, Michael; Jellusova, Julia (Frontiers in Immunology, 2025)
IntroductionCalcium (Ca2+) signaling plays a pivotal role in determining B cell fate, shaping processes such as activation, differentiation, anergy or apoptosis. Upon B cell antigen receptor activation, Ca2+ is rapidly mobilized from the endoplasmic reticulum and supplemented by Ca2+ influx from the extracellular space, ultimately driving activation of various signaling pathways required for appropriate B cell responses. Although mitochondria also harbor significant levels of Ca2+, how mitochondrial Ca2+ dynamics are regulated in B cells in response to activation or other cues remains unknown, as do the functional consequences of altered mitochondrial Ca2+ levels.MethodsChemical dyes as well as a genetically encoded Ca2+ sensor with a mitochondrial targeting sequence were used to study mitochondrial Ca2+ dynamics in response to various stimuli. Proximity ligation assays were performed to assess interaction between mitochondria and the endoplasmic reticulum. Primary mouse B cells and the Burkitt lymphoma cell line Ramos were used to study functional consequences of the loss of the Mitochondrial Calcium Uniporter.ResultsHere, we show that mitochondrial Ca2+ levels dynamically respond to cell activation, stress and metabolic cues and that mitochondrial Ca2+ uptake is largely dependent on the Mitochondrial Calcium Uniporter. Reduced mitochondrial Ca2+ uptake has a negative impact on mitochondrial activity and also affects cell signaling. These findings demonstrate that changes in mitochondrial Ca2+ contribute to shaping functional B cell responses.DiscussionThe spatial and temporal dynamics of Ca2+ accumulation within distinct subcellular compartments, particularly the cytosol, endoplasmic reticulum and mitochondria, are essential for translating extracellular and intracellular signals into specific cellular outcomes. Our study provides new insights into the regulation of Ca2+ homeostasis in B cells.